Hematoma intramural de colon ascendente de origen traumático - Cardozo, Sandra; Colet, Andrés; Odriozola, Martín; Carriquiry, Luis (Cirugía del Uruguay, 2002)
The author presents a case of intramural hematoma of colon having traumatic origin, which tiiggered intestinal occlusion and was successfully treated though a right hemicolectomy. Th_is is a rare form of anatomo-clinical traumatic affectation of colon. The importance of CAT sean in its diagnosis and treatment planning should be ighlighted